Strategies for community care aimed at vulnerable groups in Ecuador - Cruz Xiomara Peraza de Aparicio; Tania Fonseca Borges; Sandra Inda Mariño (Medisur)
The proposals of community care models are fundamentally based on the need to standardize the language and action of professionals regarding the articulation of different organizations and groups of individuals present in the community, in order to protect their health. The objective of this study is to comment on strategies aimed at an inclusive community approach for the attention of vulnerable groups. To do this, we review the issues of inequality and vulnerability, key in the 2030 Agenda. In scenarios such as rural communities in Ecuador, the community care strategy promotes actions on health problems and needs detected as prevalent, through local activities targeted at promoting health and increasing the quality of life of the inhabitants.